Molecular characterization of HCV in a Swedish county over 8 years (2002–2009) reveals distinct transmission patterns. Issue 1 (1st January 2016) - Ederth, Josefine; Jern, Camilla; Norder, Helené; Magnius, Lars; Alm, Erik; Kleverman Rognsvåg, Björg; Sundin, Carl-Gustaf; Brytting, Mia; Esbjörnsson, Joakim; Mild, Mattias
Abstract : Background: Hepatitis C virus (HCV) is a major public health concern and data on its molecular epidemiology in Sweden is scarce. We carried out an 8-year population-based study of newly diagnosed HCV cases in one of Sweden's centrally situated counties, Södermanland (D-county). The aim was to characterize the HCV strains circulating, analyze their genetic relatedness to detect networks, and in combination with demographic data learn more about transmission. Methods: Molecular analyses of serum samples from 91% (N=557) of all newly notified cases in D-county, 2002–2009, were performed. Phylogenetic analysis (NS5B gene, 300 bp) was linked to demographic data from the national surveillance database, SmiNet, to characterize D-county transmission clusters. The linear-by-linear association test (LBL) was used to analyze trends over time. Results: The most prevalent subtypes were 1a (38%) and 3a (34%). Subtype 1a was most prevalent among cases transmitted via sexual contact, via contaminated blood, or blood products, while subtype 3a was most prevalent among people who inject drugs (PWIDs). Phylogenetic analysis revealed that the subtype 3a sequences formed more and larger transmission clusters (50% of the sequences clustered), while the 1a sequences formed smaller clusters (19% of the sequences clustered), possibly suggesting different epidemics. Conclusion: We found different transmission patterns in D-county which may, from a public health perspective, have implications for how to control virus infections by targeted interventions.